Service-learning Pedagogy: A Pathway to Empowering Students as A Catalyst for Sustainable Tourism Development through Civic Engagement and Community Development - Felismonte, Isidra; Donn, Donn Enrique; U Ruiz, Merle (Media Konservasi, 2024)
The field of education for sustainable development advocates for new teaching methods that offer hands-on, engaging, and transformative learning experiences that encourage critical and systemic thinking within the framework of sustainable development. Higher education institutions strive to support the attainment of SDG 4 by promoting inclusive, fair, and high-quality education. Service-learning in higher education is in tune with the educational principles of critical and transformative pedagogy and facilitated through implementation of innovative pedagogical approaches in training professionals that will be socially critical and committed to social transformation, with the goal of achieving a larger social justice. Consequently, one of the major challenges attributed to the lack of social practice and community service in the learning environment leads to the detachment of students to the community, as well as the low social responsibility among the undergraduates. The study aimed to fill the research gap in the literature on the impact of service-learning pedagogies among students based on knowledge, attitude, and spirit and how it is correlated with professional development, personal development, social transactions. Furthermore, this study highlights how civic engagement and sustainable community development, the integral components of service-learning, contribute to and align with the principles of sustainable tourism. By connecting these elements, the research emphasizes the multifaceted benefits of service-learning in shaping socially responsible professionals and fostering sustainable tourism